2013
DOI: 10.5194/nhess-13-2065-2013
|View full text |Cite
|
Sign up to set email alerts
|

Detecting seismic IR anomalies in bi-angular Advanced Along-Track Scanning Radiometer data

Abstract: This paper presents a validation and confutation analysis using the methods of the robust satellite data analysis technique (RST) to detect seismic anomalies within the bi-angular Advanced Along-Track Scanning Radiometer (AATSR) data based on spatial/temporal continuity analysis. The distinguishing feature of our method is that we carried out a comparative analysis of seismic anomalies from bi-directional observation, which could help understanding seismic thermal infrared (TIR) anomalies. The proposed method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Nowadays, the data with low spatial resolution have been successfully used in the anomaly detection, such as NOAA OLR data with 2.5 • spatial resolution (Liebmann, 1996). The spatial scale of OLR anomaly from 1 • × 1 • NOAA data is approximately 1000-2000 km from epicenters (Xiong and Shen, 2017), which is an unexpected result for the seismic activity monitoring. However, the use of satellite data with a high spatial resolution (e.g., 1 km) can provide richer and deeper information.…”
Section: Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the data with low spatial resolution have been successfully used in the anomaly detection, such as NOAA OLR data with 2.5 • spatial resolution (Liebmann, 1996). The spatial scale of OLR anomaly from 1 • × 1 • NOAA data is approximately 1000-2000 km from epicenters (Xiong and Shen, 2017), which is an unexpected result for the seismic activity monitoring. However, the use of satellite data with a high spatial resolution (e.g., 1 km) can provide richer and deeper information.…”
Section: Other Methodsmentioning
confidence: 99%
“…Eleftheriou et al (2016) analyzed M ≥ 4 earthquakes using OLR data in Greece for 10 years. Xiong and Shen (2017) also performed preliminary work on such global statistics of pre-seismic OLR anomalies. The statistical uncertainties can serve as a priori knowledge to determine weight coefficients of precursors in a multiparametric monitoring system.…”
Section: Future Development and Perspectivesmentioning
confidence: 99%
“…A confutation test was performed to verify the appearance or absence of the POEA before or after significant earthquakes over the same area (Di Bello et al, 2004;Genzano et al, 2009;Tramutoli et al, 2013;Xiong et al, 2013;Lisi et al, 2015;Khalili et al, 2019). As shown in Figure 6, most of the POEAs were only observed once within 90 days before and 25 days after the related earthquake, except for eight of the 35 selected seismic events .…”
Section: Relationship Between Olr E Index Variations and Seismicitymentioning
confidence: 99%
“…Analysis of the thermal anomaly phenomenon using satellite techniques for monitoring seismically active regions has been carried out since the 1980s (Gorny et al, 1988). Many studies have reported that thermal anomalous space-time transients were detected in the OLR or thermal infrared radiation (TIR) before and/or during the earthquake preparation stage (Tronin, 1996(Tronin, , 2000Tramutoli et al, 2001Tramutoli et al, , 2005Tramutoli et al, , 2009Tramutoli et al, , 2013Di Bello et al, 2004;Ouzounov and Freund, 2004;Ouzounov et al, 2006Ouzounov et al, , 2007Pulinets et al, 2006;Genzano et al, 2007Genzano et al, , 2009Genzano et al, , 2010Genzano et al, , 2015Pulinets and Dunajeck, 2007;Aliano et al, 2008a,b;Pergola et al, 2010;Xiong et al, 2010Xiong et al, , 2013Xiong et al, , 2015Pulinets and Ouzounov, 2011;Jing et al, 2012;Lisi et al, 2015;Xiong and Shen, 2017;Khalili et al, 2019Khalili et al, , 2020. The main mechanisms proposed for the temperature increase are (1) the emission of diffuse gases (e.g., radon and CO 2 ) leading to a local greenhouse effect or near-ground air ionization to release heat (Tronin, 2002;Pulinets et al, 2006;Tramutoli et al, 2009Tramutoli et al, , 2013Koll and Cronin, 2018) and (2) positive hole charge or the excitation of an electric field from the stressed rock resulting in infrared emission and energy flow (Ouzounov and Freund, 2004;Freund, 2007a,b;Freun...…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out to analyze thermal infrared (TIR) anomalies appearing in the area of earthquake occurrence a few days before the seismic shock. These studies analytically compare images of pre (vs. post) earthquake satellite TIR imagery (Tronin et al 2002;Shen 2013;Xie et al 2013); study outgoing longwave radiation (OLR) data and identify anomalous variations prior to a number of medium to large earthquakes (Defu et al 1997;Ouzounov et al 2007;Xiong et al 2010a, b;Jing et al 2013;Xiong et al 2013); perform a multispectral thermal infrared component analysis during earthquakes using land surface temperature (LST) (Ouzounov and Freund 2004;Tronin et al 2004); or assess the anomalous surface latent heat flux (SLHF) peaks a few days prior to the earthquake event (Cervone et al 2004(Cervone et al , 2005Qin 2013).…”
Section: Introductionmentioning
confidence: 99%